Development of a Self-Service Bookshelf System for Public Spaces Using RFID Technology integrates with Mobile Apps - Nazhra Hamdani; Rizka Hadelina (Universitas Andalas, 2026)
Reading culture is an indicator of a country's public interest in knowledge, creativity, and critical thinking skills. Based on research by the Program for International Student Assessment (PISA), Indonesia is ranked at the bottom of the 80 participating countries. Furthermore, Indonesia's limited book production and relatively high book prices, especially for the lower-middle class, are also contributing factors. Many solutions have been proposed to improve literacy in Indonesia, including the digitization of libraries. This research aims to develop a self-service bookshelf for public spaces, such as waiting rooms, train stations, bus stops, offices, classrooms, and other public spaces. An RFID-based system will be used to read and write data. For security, a system will be implemented that grants access only to registered users. Furthermore, the system will be equipped with a mobile application to provide users with real-time information regarding book borrowing and returns. This system uses the RFID Reader CT-1808 to read RFID tags attached to books as book identifiers. Based on testing, it was found that, despite having anti-collision, this reader still requires a distance between tags, not being able to be close to each other, namely the optimal 5 cm. In addition, this reader has a blind spot that needs to be considered, so the placement of books (tags) is very important. In general, this bookshelf can be accessed by visitors via a QR Code obtained during registration using the mobile app. Visitors can now borrow and return books independently, and their history can be accessed in the mobile app.